2004
DOI: 10.1007/bf02829442
|View full text |Cite
|
Sign up to set email alerts
|

The solutions of then-dimensional Bessel diamond operator and the Fourier-Bessel transform of their convolution

Abstract: In this article, the operator ✸ k B is introduced and named as the Bessel diamond operator iterated k times and is defined by. . , n, k is a non-negative integer and n is the dimension of R + n . In this work we study the elementary solution of the Bessel diamond operator and the elementary solution of the operator ✸ k B is called the Bessel diamond kernel of Riesz. Then, we study the Fourier-Bessel transform of the elementary solution and also the Fourier-Bessel transform of their convolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Let S α (x) and R β (x) be defined by (4) and (5) respectively. Then S α (x) * R β (x) exists and it is a tempered distribution.…”
Section: Lemma 26mentioning
confidence: 99%
See 1 more Smart Citation
“…Let S α (x) and R β (x) be defined by (4) and (5) respectively. Then S α (x) * R β (x) exists and it is a tempered distribution.…”
Section: Lemma 26mentioning
confidence: 99%
“…Later, Hüseyin Yildirim, Mzeki Sarikaya and SerminÖztürk [5] introduce the Bessel diamond operator ♦ k B iterated k−times, defined by…”
Section: Introductionmentioning
confidence: 99%
“…Yildirim, Sarikaya and Ozturk [7] have showed that (−1) t S 2t (a) * R 2t (a) is the solution of the ♦ t B (−1) t S 2t (a) * R 2t (a) = δ , where…”
Section: Introductionmentioning
confidence: 99%
“…Yildirim, Sarikaya and Ozturk [3] showed that the function u(x) = (−1) k S 2k (x) * R 2k (x) is the unique elementary solution for the operator ♦ k B , where * indicates convolution, and R 2k (x), S 2k (x) are defined by (1.4) and (1.5) respectively, that is,…”
Section: Introductionmentioning
confidence: 99%